2006
DOI: 10.1089/thy.2006.16.967
|View full text |Cite
|
Sign up to set email alerts
|

Study of Serum Antibodies Against Three Eye Muscle Antigens and the Connective Tissue Antigen Collagen XIII in Patients with Graves' Disease With and Without Ophthalmopathy: Correlation With Clinical Features

Abstract: Calsequestrin and collagen XIII antibodies are the most specific to TAO, whereas antibodies against G2s, and to a lesser extent Fp, are also markers of ophthalmopathy, but less reliable. These results are unique in that it is the first time the significance of a panel of three candidate eye muscle antibodies and a connective tissue antibody have been evaluated in the same patients with ophthalmopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 25 publications
2
52
1
1
Order By: Relevance
“…Notably, in patients with TAO, alpha fodrin may be one of the autoantigens involved in both the salivary glands and orbit (16) and thus may have been responsible for the symptoms observed in our patient. In addition, calsequestrin, collagen XIII, IGF-1 receptor and TSH receptor have been proposed to be antigens involved in the pathogenesis of TAO (17,18). Further investigations are warranted to identify common autoantigens among autoimmune thyroid diseases, ocular adnexal diseases and IgG4-RD.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in patients with TAO, alpha fodrin may be one of the autoantigens involved in both the salivary glands and orbit (16) and thus may have been responsible for the symptoms observed in our patient. In addition, calsequestrin, collagen XIII, IGF-1 receptor and TSH receptor have been proposed to be antigens involved in the pathogenesis of TAO (17,18). Further investigations are warranted to identify common autoantigens among autoimmune thyroid diseases, ocular adnexal diseases and IgG4-RD.…”
Section: Discussionmentioning
confidence: 99%
“…in chronic lymphocytic thyroiditis. In these patients factors leading to pathologic changes may include antibodies against ocular muscle antigens: calsequestrin, collagen XIII, flavoprotein (Fp) and protein G2s [24]. Oxidative stress may also have a negative influence on the course of TAO.…”
Section: Pathogenesis Of Thyroid-associated Ophthalmopathymentioning
confidence: 99%
“…18 As the factors concerning the onset, severity, and drug responsiveness of TAO are yet uncertain and the role that hyperthyroidism management may play on TAO's emergence and development are also unclear, TAO management remains a key research topic. 19 In this review, we found therapeutic indication for TAO in 53 out of 167 patients. The remainders who showed no medical signs judging from CAS and MRI had missed their particular window of responsiveness to treatment mainly due to a gap between pathological activities and clinical symptoms.…”
Section: Discussionmentioning
confidence: 94%